STUDENT’S NUMERACY PROFILE AND SELF CONFIDENCE CHARACTER IN THE ERA OF “MERDEKA BELAJAR” IN ELEMENTARY SCHOOLS - Eka Setiawati; Neni Mariana (Universitas Majalengka, 2025)
This study aims to identify the numeracy skills and self-confidence profiles of fifth-grade elementary school students in the Merdeka Belajar era. The research employs a quantitative descriptive approach, using numeracy tests and self-confidence measurement scales as the primary instruments. The numeracy test consists of five questions aligned with key indicators of geometry, including spatial visualization and area and perimeter calculations, while the self-confidence scale assesses six aspects, such as initiative, public speaking ability, and resilience in the face of challenges. Data were analyzed using the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing, complemented by descriptive statistics, including percentages and averages. The findings reveal that the average numeracy score is 60.42, categorized as low, with 68.6% of students in the low category, 22.8% in the medium category, and only 8.6% in the high category. Similarly, self-confidence levels are low for 34.3% of students, medium for 28.6%, and high for 22.9%. Further analysis shows that limited self-confidence significantly hampers students’ ability to solve numeracy problems, especially in spatial reasoning and geometric calculations. To address these challenges, it is recommended that educators adopt innovative teaching strategies, such as utilizing interactive tools like GeoGebra, incorporating collaborative learning methods, and implementing real-life problem-solving tasks to build both numeracy skills and self-confidence. These strategies align with the Merdeka Belajar framework, promoting active and meaningful learning experiences that cater to diverse student needs.